2015
DOI: 10.1161/circep.114.002306
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Rotors With Minimal Electrodes

Abstract: Background-High-frequency periodic sources during cardiac fibrillation can be detected by phase mapping techniques.To enable practical therapeutic options for modulating periodic sources (existing techniques require high density multielectrode arrays and real time simultaneous mapping capability), a method to identify electrogram morphologies colocalizing to rotors that can be implemented on few electrograms needs to be devised. Method and Results-Multichannel ventricular fibrillation electrogram data from 7 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…These rotors are believed to be centres where the ventricular arrhythmia originates [30][31][32][33]. Rotors are of special clinical interests as detecting them and tracking them could lead to termination of VA through ablation [2,34]. A conference proceeding by our group revealed that there exists different distributions of a few repeating electrogram signal patterns during an arrhythmic episode [35].…”
Section: Current Researchmentioning
confidence: 99%
“…These rotors are believed to be centres where the ventricular arrhythmia originates [30][31][32][33]. Rotors are of special clinical interests as detecting them and tracking them could lead to termination of VA through ablation [2,34]. A conference proceeding by our group revealed that there exists different distributions of a few repeating electrogram signal patterns during an arrhythmic episode [35].…”
Section: Current Researchmentioning
confidence: 99%
“…Several methods were introduced to help map rotors using engineering techniques in both time and frequency domain [54][55][56][57][58]. Some of these methods are specifically designed to use conventional MPDCs such as a Lasso catheter, aiming to outperform the limitations of the current EP systems available for identifying rotors.…”
Section: Computer-aided Technologies For Atrial Fibrillationmentioning
confidence: 99%
“…The relevant methods available in the literature for locating rotors involve deterministic, noniterative solutions using time-domain and frequency-domain characteristics [54][55][56][57][58]. The developed method uses a Bayesian filtering approach to search for the rotors by iteratively guiding an MPDC toward the center of a rotor.…”
Section: Computer-aided Technologies -Applications In Engineering Andmentioning
confidence: 99%
“…In addition, bipolar electrograms are the most commonly used recording modality in clinical electrophysiology, making these signals readily available for entropy analysis whilst also providing a direct and interpretable translation to what is seen clinically. Lastly, high bipolar electrogram Shannon entropy (ShEn) has been demonstrated by our group to be associated with the pivot of rotors [4,18,19], and subsequently entropy-based identification of the rotor pivot has been independently observed by multiple groups using a variety of entropy-based approaches, and in multiple model systems [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%